Targeting Dermal Fibroblast Subtypes in Antifibrotic Therapy: Surface Marker as a Cellular Identity or a Functional Entity? - Huang, Xin; Khoong, Yimin; Han, Chengyao; Su, Dai; Ma, Hao; Gu, Shuchen; Li, Qingfeng; Zan, Tao (Frontiers in Physiology, 2021)
Fibroblasts are the chief effector cells in fibrotic diseases and have been discovered to be highly heterogeneous. Recently, fibroblast heterogeneity in human skin has been studied extensively and several surface markers for dermal fibroblast subtypes have been identified, holding promise for future antifibrotic therapies. However, it has yet to be confirmed whether surface markers should be looked upon as merely lineage landmarks or as functional entities of fibroblast subtypes, which may further complicate the interpretation of cellular function of these fibroblast subtypes. This review aims to provide an update on current evidence on fibroblast surface markers in fibrotic disorders of skin as well as of other organ systems. Specifically, studies where surface markers were treated as lineage markers and manipulated as functional membrane proteins are both evaluated in parallel, hoping to reveal the underlying mechanism behind the pathogenesis of tissue fibrosis contributed by various fibroblast subtypes from multiple angles, shedding lights on future translational researches.